Kewenangan Aparat Pengawasan Intern Pemerintah Dalam Menyatakan Kerugian Keuangan - Wirabuana, Zainuddin; Nirahua, Salmon Eliazer Marthen; Bakarbessy, Andress Deny (Pusat Kajian Korupsi Fakultas Hukum Universitas Pattimura, 2023)
Introduction: The Government Internal Supervisory Apparatus (APIP) is an internal supervisor who carries out the task of administering government affairs in the field of state/regional financial supervision and national development. Law enforcement officials often use the results of the APIP audit as evidence in trials of corruption cases, as well as the panel of judges at the Ambon District Court continues to accept the results of calculations and provide expert opinions in trials. Purposes of the Research: Analyzing juridically through reviewing laws and regulations relating to the authority of the Government Internal Supervisory Apparatus in declaring state financial losses, and analyzing the relationship between supervisory and auditing institutions (BPK and APIP) in determining and declaring state financial losses. Methods of the Research: The research method used is normative, that is, research that primarily examines positive legal provisions and legal principles, explain and predicts in the direcrion of future legal developments. Results of the Research: The results of the research show that (1) APIP remains authorized to conduct investigative audits, audit calculations of state financial losses and provide expert testimony at trial, (2) There is no legal protection that regulates the pattern of confidential audit results relations between APIP and BPK. Therefore, it is necessary to enact laws and regulations that reinforce the role of each supervisory and examiner institution to create legal certainty and prevent overlapping authorities.